2007
DOI: 10.1002/anie.200700159
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Synthesis of Primary Allylic Amines from Allylic Alcohols: Sulfamic Acid as Ammonia Equivalent

Abstract: Two for the price of one: Sulfamic acid serves not only as a nitrogen source but also as an in situ activator of hydroxy groups in the first direct iridium‐catalyzed synthesis of primary allylic amines from allylic alcohols (see scheme; cod=cycloocta‐1,5‐diene). The reaction is catalyzed by a commercially available iridium complex and a phosphoramidite‐based bidentate phosphorus–olefin ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
149
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(153 citation statements)
references
References 74 publications
0
149
0
4
Order By: Relevance
“…The kinetic study of the Rh/L43 system in ECA, revealed that the catalytic activity with L43 to be intermediate to that of diphosphines and dienes [130]. Good activities and enantioselectivities were obtained with ligands L44 [131], amidophosphine-alkene L45 [132] (first synthesized by Carreira [133]) and with the chiral phosphine-olefin L46 [134].…”
Section: Mixed Donor Ligandsmentioning
confidence: 95%
See 1 more Smart Citation
“…The kinetic study of the Rh/L43 system in ECA, revealed that the catalytic activity with L43 to be intermediate to that of diphosphines and dienes [130]. Good activities and enantioselectivities were obtained with ligands L44 [131], amidophosphine-alkene L45 [132] (first synthesized by Carreira [133]) and with the chiral phosphine-olefin L46 [134].…”
Section: Mixed Donor Ligandsmentioning
confidence: 95%
“…<20%). Similar to the addition of organotitanates, ClSiMe 3 is necessary to activate the arylzinc reagents, the product being obtained as the corresponding silyl enol ether (133). For this transformation, arylzinc reagents were superior to organoboron and organotitanium reagents.…”
Section: Rh-catalyzed Eca Organotitanium and Organozinc Reagentsmentioning
confidence: 99%
“…The phenyl ether products were also isolated in mid-to-high enantiomeric excess. More recently, Carreira and coworkers reported the reactions of sulfamic acid with branched allylic alcohols to form branched primary allylic amines [106]. One enantioselective reaction was disclosed, and the product was isolated in 70% ee when using a 5H-dibenzo[b, f ]azepine-derived phosphoramidite with [Ir(COE) 2 Cl] 2 (Scheme 33).…”
Section: Allylic Substitution Of Branched Allylic Estersmentioning
confidence: 97%
“…Accordingly, Carreira and co-workers pioneered the field by describing the use of sulfamic acid (H 2 NSO 3 H, 13) as an ammonia equivalent, in the preparation of primary allylamines with alcohols. 16 An elegant approach for the direct utilization of unactivated allylic alcohols as electrophilic precursors was documented by Carreira and co-workers though the asymmetric dynamic kinetic resolution (DKR) of racemic secondary alcohols with primary alkyl alcohols 17. 17 Once again, the chiral E-iridium(I) complex emerged as a competent promoter for the preparation of optically active unsymmetrical allyl ethers 18.…”
Section: C-n and C-o Bond-forming Reactionsmentioning
confidence: 99%